Changes in Surface Temperatures and Their Relationship with Forest Fires in Antalya Province - Yasin Furkan Şenlik; Erkan Yılmaz (Doğal Afetler ve Çevre Dergisi)
In this study, the distribution and trends of the average surface temperature of Antalya province between 2000-2022 are analyzed. It was also investigated whether there is a significant relationship between surface temperatures and forest fires between 2003-2021. The lowest surface temperatures were found in Bey Mountains and Geyik Mountains due to the effect of elevation. The warmest places are Aksu Plain, Antalya Tufa Plateau and Kestel Polje System. In the study area, there is generally a decreasing trend in surface temperatures during daytime hours, while there is an increasing trend at night. 11 fires were selected for examination of the relationship between surface temperatures and wildfire. As a result of the regression analysis applied to the long years surface temperatures of the fire exit points, it was observed that there was no significant temperature increase at any fire exit point during the hottest hour of the day. In the last 10 days before the fires, only 1 fire was found to have a temperature increase trend. In the 23-year period, a total of 5076 forest fires occurred in Antalya, 87% of which were caused by human activity. As a result, it is understood that the main factor affecting forest fires in Antalya is anthropogenic and that surface temperatures can only indirectly affect forest fires.